The range of causatives with fàchere ‘make’ in Sardinian: - Eva-Maria Remberger (Isogloss, 2024)
Sardinian has several types of make-construction: the analytic causative constructions corresponding to French faire-inf (FI) and faire-par (FP); subject control constructions similar to the colloquial idiomatic use of the pronominal Italian verb farcela ‘be able to, to manage’ (a kind of dynamic ability); and particular impersonal constructions that express the deontic modality of possibility. Furthermore, there are several lexicalized expressions that involve make, similar to Italian far vedere ‘to show’ (lit. ‘to make see’). The impersonal construction, which I call the “impersonal causative”, is of particular interest in this paper: It always selects an infinitive (not inflected, which would be possible at least in some varieties of Sardinian), introduced by a; apparently, it shows transparency effects, but it must nevertheless be interpreted as a biclausal structure; it is, in principle, only possible with the third person of the verb make; with regard to its interpretation it encodes modal possibility and is thus more related to (less strong causative) LET than to strong causative MAKE; and it shows up in two different types, at least in some varieties, with or without number agreement (the latter also with an overt subject in a personal infinitive), which has interesting consequences for the interpretation of the argument structure of MAKE.